MODEL PEMBINAAN PKL DI KOTA SURAKARTA DENGAN PENDEKATAN EDUKASI LEWAT BIMBINGAN DAN PENYULUHAN (UPAYA MENDUKUNG PROGRAM AKSI KOTA KREATIF) - Joko Suwandi; Budi Sutrisno (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2018)
The sustainable issue of street vendor (PKL) management in Surakarta needs a programed supervision model in order to make PKL growing and having greater impact. The research aimed to arrange a PKL coaching model which is well programmed and sustainable to make PKL become a power of stable economic people and capable to suppport many city development programs including The City Creatif Action Program year 2017-2021. This improvisation research studied the first year research findings with the colleagues who have responsibility in PKL supervision, observer and practitioner, in turn developing a programed and sustainable model. The critical analysis was used to analyze the data which is analyze the weaknesses and strength a model so that it become the most suitable model. The coaching is arranged as follows: (1) The implementation syntax consists of: bring around and forming attitude leads up to care and aware attitude, expand knowledge transformation, capability, basic skills, and intellectual skill improvement in order to develop initiative and innovation skill to reach an autonomy. (2) The coaching scope consists of: a) arrange a stable business environment, b) capital assistance, c) business protection, d) partnership development, e) training, f) establish special institution, g) promotion development, h) develop facilities and infrastructure. (3) Coaching PKL based on counseling and guidance. (4) Implementation of counseling and developing PKL consists of: a. Counseling and developing in production and processing, b. Marketing, c. Human resources, d. technology.